1989
DOI: 10.1128/jvi.63.9.4110-4114.1989
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the human immunodeficiency virus vpr open reading frame

Abstract: Mutations were introduced by recombinant DNA techniques into the vpr open reading frame of an infectious molecular clone of human immunodeficiency virus type 1. The effect of these changes on the replicative and cytopathologic properties of the virus recovered from transfected cells was studied in several human CD4+ lymphocyte cell lines. In all cases, mutant viruses were infectious and cytopathic. However, when a low-input dose was used, mutants grew significantly more slowly than the wild-type virus. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(71 citation statements)
references
References 37 publications
6
64
0
Order By: Relevance
“…Among them, Vpr and its duplicated gene product Vpx (24) are unique because they are selectively incorporated in the viral particles at molar quantities equivalent to those of Gag proteins (3,9,28). Genetic studies have shown that Vpr and Vpx are dispensable for replication in human T cell lines (4,10,17), but essential for replication in primary macrophages (2,7,10,25). Furthermore, Vpr has been shown to be required for efficient replication and persistence of simian immunodeficiency virus (SIV) in rhesus monkeys (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Vpr and its duplicated gene product Vpx (24) are unique because they are selectively incorporated in the viral particles at molar quantities equivalent to those of Gag proteins (3,9,28). Genetic studies have shown that Vpr and Vpx are dispensable for replication in human T cell lines (4,10,17), but essential for replication in primary macrophages (2,7,10,25). Furthermore, Vpr has been shown to be required for efficient replication and persistence of simian immunodeficiency virus (SIV) in rhesus monkeys (11).…”
mentioning
confidence: 99%
“…We decided to test this idea by using bacterial chloramphenicol acetyltransferase (CAT) as a fusion partner. A pSRa (23) expression vector encoding CAT fused to the N-terminus of HIV-1 Vpr was transfected into SW480 cells along with a vpr-negative HIV-1 infectious clone pNLAf2 (17). Virions produced in the supernatants were pelleted by centrifugation on a 20% sucrose cushion and further sedimented in linear gradients of 20% to 60% sucrose.…”
mentioning
confidence: 99%
“…Vpr. The 14-Kd, 96-amino-acid HIV-1 encoded protein Vpr (viral protein R) [50,51], plays several roles in the replication cycle of this retrovirus. Thus, it has been proposed that Vpr regulates the nuclear import of the preintegration complex (PIC) carrying the proviral DNA, the viral integrase, and other viral and cellular proteins.…”
Section: 1mentioning
confidence: 99%
“…While the Vpr protein is quite well conserved within the SIVagm group and also among HIV-1, HIV-2, and SIVsm, little is known about its function. Until now, Vpr has not seemed to be essential for replication in cell culture (15,39). Studies of SIVmac Vpr mutants have not yet demonstrated that Vpr is absolutely essential for disease progression in vivo (31).…”
Section: Comparisons Between Regulatory Proteins Of D30 and D42 Straimentioning
confidence: 99%